2018
DOI: 10.1002/jcp.27992
|View full text |Cite
|
Sign up to set email alerts
|

Opioid receptors and opioid peptides in the cardiomyogenesis of mouse embryonic stem cells

Abstract: The stimulation of myocardium repair is restricted due to the limited understanding of heart regeneration. Interestingly, endogenous opioid peptides such as dynorphins and enkephalins are suggested to support this process. However, the mechanism—whether through the stimulation of the regenerative capacity of cardiac stem cells or through effects on other cell types in the heart—is still not completely understood. Thus, a model of the spontaneous cardiomyogenic differentiation of mouse embryonic stem (mES) cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…ese findings demonstrate clearly that nalbuphine at 0.4 mg/kg/h does not influence systolic function of healthy dogs anesthetized with sevoflurane. Previous studies showed that mammalian myocardium can be directly influenced by opioids, given the presence of opioid receptors μ, σ and κ [3][4][5]. Kappa receptors seem to be the main regulators of cardiac function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ese findings demonstrate clearly that nalbuphine at 0.4 mg/kg/h does not influence systolic function of healthy dogs anesthetized with sevoflurane. Previous studies showed that mammalian myocardium can be directly influenced by opioids, given the presence of opioid receptors μ, σ and κ [3][4][5]. Kappa receptors seem to be the main regulators of cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that mammalian myocardium has opioid receptors μ, σ, and κ [3][4][5]. One of the most important myocardium opioid receptors is the kappa.…”
Section: Introductionmentioning
confidence: 99%
“…The mESC line R1 (ATCC ® SCRC-1011™) was cultivated as described previously [15]. Cells were routinely tested for the presence of Mycoplasma contamination (RT-qPCR).…”
Section: Cultivation and Treatment Of Mescmentioning
confidence: 99%
“…A total of 20 µg of protein lysates were loaded on SDSpolyacrylamide gel. Immunoblot analyses were performed as presented previously [15]. The following primary antibodies were used to detect particular proteins: rabbit anti-OCT-3/4 (#9081, 1:1000) from Santa Cruz Biotechnology (Dallas, TX, USA), rabbit anti-NANOG (#8822, 1:1000), rabbit anti-SOX2 (#23064, 1:1000), rabbit anti-phospho-STAT3 (#9145, Tyr705, 1:2000), mouse anti-STAT3 (#9139, 1:1000), anti-total/phospho-ERK1/2 (#4696, 1:2000/#4377, 1:1000), anti-total/phospho-AKT (#2920, 1:2000/#4056, 1:1000) (all from Cell Signaling Technology, Danvers, MA, USA), mouse anti-Vinculin (V9264, 1:10000; Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Protein Expression Analysis By Western Blot Techniquementioning
confidence: 99%
See 1 more Smart Citation